Food narratives: meanings of food and nutrition insecurity in the elderly - Santos, Laíse Rodrigues dos (2023)
The elderly population has memories that reflect different moments of food uncertainties and public policies aimed at food. In this sense, this work aims to analyze the food history of the elderly, especially with regard to the meanings of food and nutritional insecurity in the lives of these subjects, as well as the implication in their current food choices. The work is developed through autobiographical narratives in the socio-historical perspective. The results demonstrated the coexistence in the lines of denial of hunger and the strategies used in moments of food and nutritional insecurity experienced by the participants and also by their families. Food cravings are satisfied even in the different previous moments and their reflection in the current diet. In view of the observed, it is highlighted that listening to the subject allows reflection and perception of food in addition to the biological field.